Electrical and structural characterization of GaN-based transistor structures - Loo, Nicholas Yujun (2016)
Abstract There are primarily two parts to this project. The first part consists of understanding High Electron Mobility Transistors (HEMT), Two Dimensional Electron Gas (2DEG), and Gallium Nitride properties. In the second part, Hall Effect Measurement, Atomic Force Microscopy (AFM) and Four Point Probe measurements and analysis are described in order to better understand the electrical properties of the AlGaN or GaN based samples. The second part is the experiment to observe the device’s resistance value under the presence of different gases and at different temperature. In order to proceed with this part, training has been done on the Gas Sensor Characterisation System. The gases used for this portion of the project are Carbon Dioxide (CO2), Nitrogen Dioxide (NO2) and Ammonia gas (NH3). After testing with the gases, we found that the sample device does not react to carbon dioxide at room temperature. However, the device undergoes changes in resistance value when exposed to ammonia and nitrogen dioxide at room temperature. At 100 oC, the device was found to react to all three gases. The device is then placed under ammonia gas and studied on its behaviour when exposed to high temperature. The device was found to have similar behaviour from 100 oC to 500 oC (albeit at different resistance value) and erratic behaviour at 600 oC. More experimentation should be conducted to uncover the results obtained from the 600 oC test.